Duplication of genes encoding non-clathrin coat protein -COP in vertebrate, insect and plant evolution. - Hahn, Y.; Lee, Y.J.; Yun, J.H.; Yang, S.K.; Park, C.W.; Mita, K.; Huh, T.L.; Rhee, M.; Chung, J.H. (FEBS Letters, 2000)
Coatomer is a major component of COPI vesicles and consists of seven subunits. The gamma-COP subunit of the coatomer is believed to mediate the binding to the cytoplasmic dilysine motifs of membrane proteins. We characterized cDNAs for Copg genes encoding gamma-COP from mouse, zebrafish, Drosophila melanogaster and Bombyx mori. Two copies of Copg genes are present in vertebrates and in B. mori. Phylogenetic analysis revealed that two paralogous genes had been derived from a single ancestral gene by duplication independently in vertebrates and in B. mori. Mouse Copg1 showed ubiquitous expression with the highest level in testis. Zebrafish copg2 was biallelically expressed in hybrid larvae in contrast to its mammalian ortholog expressed in a parent-of-origin-specific manner. A phylogenetic analysis with partial plant cDNA sequences suggested that copg gene was also duplicated in the grass family (Poaceae).